2021
DOI: 10.19040/ecocycles.v7i2.201
|View full text |Cite
|
Sign up to set email alerts
|

The effect of biochar application on soil properties and growth of the model plant Zea mays

Abstract: The classic way of land cultivation means the use of inorganic fertilizers that are salts that dissolve rapidly in a short time and improve soil fertility. This process negatively affects soil salinity and the life of microorganisms. The use of biochar as a soil conditioner is a promising solution. The aim of the work is to enrich the properties of less fertile soils and to enhance the growth of the model plant Zea mays (corn) by biochar application. We used four different soil types commonly spread in the Cze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…We have reported the direct relation of biochar particle size fraction and the content of organic matter (and with the corresponding residual inorganic content), organic carbon and partially also organic nitrogen (data are shown in Table 4). The higher capability of the finest biochar particle to release inorganic ions has a direct effect on the physicochemical properties (pH, conductivity, ionic strength, water and ion-exchange capacity) of the surrounding soil [24,37,38]. In our previous study, we observed a minor increase in pH and a more significant increase in conductivity with a decrease in biochar particle fineness.…”
Section: Ph Conductivity Macroelements and Microelements Contentmentioning
confidence: 75%
See 1 more Smart Citation
“…We have reported the direct relation of biochar particle size fraction and the content of organic matter (and with the corresponding residual inorganic content), organic carbon and partially also organic nitrogen (data are shown in Table 4). The higher capability of the finest biochar particle to release inorganic ions has a direct effect on the physicochemical properties (pH, conductivity, ionic strength, water and ion-exchange capacity) of the surrounding soil [24,37,38]. In our previous study, we observed a minor increase in pH and a more significant increase in conductivity with a decrease in biochar particle fineness.…”
Section: Ph Conductivity Macroelements and Microelements Contentmentioning
confidence: 75%
“…The main aim of the research was the investigation of the role of biochar particle size and texture on the crucial characteristics important for its possible agronomical utilization as a soil conditioner. The literature provides a detailed discussion on the importance of an appropriate selection of source biomass feedstock [2,17,33,34], biomass pre-pyrolysis treatment [35] and pyrolysis conditions [33,36,37] as the important prerequisites driving the final properties of produced biochar. The lack of information on the corresponding effects of particle size and biochar texture was already pointed out in our previously published research [25].…”
Section: Resultsmentioning
confidence: 99%
“…Kocsis et al (2022) stated that biochar had a high porosity and could improve the physico-chemical and biological properties of the soil. In line, Sovova et al (2021) found that biochar had a good influence on improving the soil properties of regosol. Further, Das et al (2021) suggest the application of biochar to the soil can provide agronomic be nefits, support cro p yi eld improvement, and improve soil quality and health.…”
Section: Introductionmentioning
confidence: 77%
“…Suo et al [34] compared the WHC of biochar samples originating from a wide variety of biomass feedstock, and they summarized that besides woody biomass, corn residues-based biochar also showed high WHC. The observed values of WHC, together with well-developed SSA and porosity of both woodcut and corn biomass feedstock-based biochar samples created from these materials suitable candidates for agrochemical applications as soil supplements as this specific biochar property significantly improve soil water holding capacity mainly in the case of soil samples with lower content of soil organic matter [22,26].…”
Section: Biochar Characterizationmentioning
confidence: 93%
“…The high pH of biochar originating from commercial compost is connected with the presence of inorganic impurities even in original feedstock biomass. The high conductivity of biochar, together with its neutral or slightly alkaline pH response (pH between 7 and 10), is important for the agronomical application as these parameters guarantee the higher content of nutrients, which are accessible for plants after biochar application into the soil [10,26]. On the other hand, the low conductivity of biochar originating from woodcuts is not optimal for agricultural applications.…”
Section: Biochar Characterizationmentioning
confidence: 99%